2007
DOI: 10.1097/jsa.0b013e318042af30
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lateral Retinacular Release in the Treatment of Patellar Instability

Abstract: In the last 2 decades many authors have described the use of an isolated lateral retinacular release for the treatment of patellar instability. This review analyzes the published long-term results of this procedure for the treatment of patellar instability. The isolated use of a lateral retinacular release of the patella has not proven to be of long-term benefit for the treatment of patellar instability. It may be used as an adjunct procedure to a proximal or distal realignment of the extensor mechanism. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 27 publications
0
69
0
5
Order By: Relevance
“…Como complicação dessa liberação, podemos nos deparar com a subluxação patelofemoral medial, inclusive em sua forma oculta (29) . Essa entidade pode contribuir com os maus resultados obtidos após o procedimento de liberação retinacular lateral (30) . Dessa forma, a suspeita diagnóstica de subluxação medial iatrogênica da patela deve sempre estar presente no raciocínio do ortopedista, especialmente nos casos de resultados insatisfatórios.…”
Section: Discussionunclassified
“…Como complicação dessa liberação, podemos nos deparar com a subluxação patelofemoral medial, inclusive em sua forma oculta (29) . Essa entidade pode contribuir com os maus resultados obtidos após o procedimento de liberação retinacular lateral (30) . Dessa forma, a suspeita diagnóstica de subluxação medial iatrogênica da patela deve sempre estar presente no raciocínio do ortopedista, especialmente nos casos de resultados insatisfatórios.…”
Section: Discussionunclassified
“…Factors such as core weakness, increased valgus knee alignment, generalized ligamentous laxity, increased foot pronation, and increased femoral anteversion have shown to be factors that can contribute to anterior knee pain and patella instability. 2 In addition, weakness of the vastus medialis obliquus (VMO) is thought to be an important factor resulting in patellar subluxation and dislocation. Understanding the relationship between VMO weakness and patellar tracking may be useful in diagnosis, treatment, and prevention of patellar subluxation.…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6][7] During the acute stage, aspiration of effusion may allow the patient to regain quadriceps strength and control. 2 However, if a patient has a loose body after a dislocation, Colvin and West 4 recommend arthroscopy for removal or possible fixation of the fracture fragment, in which case a medial repair will usually be performed simultaneously. Nonoperative treatment includes physical therapy, focusing on strengthening of the gluteal muscles and the VMO, and patellar taping or bracing.…”
Section: Introductionmentioning
confidence: 99%
“…Authors found fair results only among patients with pre-existing chondromalacia of the patella 41 . Panagopoulos et al followed 25 patients after MPFL reconstruction for an average release may be used as an adjunct to proximal or distal realignment procedures 38 . One complication of isolated lateral release is medial patellar instability.…”
Section: Non-operative Managementmentioning
confidence: 99%
“…One complication of isolated lateral release is medial patellar instability. An over-release of the lateral retinaculum may cause the patella to track excessively medially and potentially subluxate or dislocate in that direction 38 . Other complications of lateral release include post-operative infection, haematoma formation, and paradoxical worsening lateral instability.…”
Section: Non-operative Managementmentioning
confidence: 99%